Influencia del sexo de las larvas hospedantes en la produccion "in vivo" de Baculovirus - Santiago-Alvarez, C.=700 1 Vargas Osuna, E.; Gonzalez Santos, M.D.; Aldebis, H.K.
(Es, En)
ilus., 21 ref.
Keywords: BACULOVIRIDAE; AGROTIS SEGETUM; SPODOPTERA LITTORALIS; VIRUS DE LA GRANULOSIS; VIRUS POLIEDROSIS NUCLEAR; ESPAÑA